Rodinný dům Pohořelice - Čech, Patrik (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem této bakalářské práce je zpracování projektové dokumentace pro provádění stavby rodinného domu v Pohořelicích. Dům je navržen jako dvoupodlažní. Konstrukční systém je stěnový, tvořený z pórobetonových tvárnic. Objekt je založen na základových pasech z prostého betonu. Stropní konstrukce jsou navrženy jako monolitické železobetonové. Objekt je zastřešen plochou jednoplášťovou střechou. Vnější stěny jsou zatepleny kontaktním zateplovacím systémem.

The subject of this bachelor's thesis is the design of project documentation for the construction of a family house in Pohorelice. The house is designed as two floors. The structural system is wall, made of aerated concrete blocks. The building is based on the foundation strips of plain concrete. The ceiling structures are designed as monolithic reinforced concrete. The building is covered with a flat single-skin roof. The external walls are insulated with a contact insulation system.
Family House Pohořelice
Keywords: rodinný dům; plochá střecha; pórobetonové zdivo; monolitický strop; garáž; family house; flat roof; aerated concrete blocks; monolithic ceiling; garage